2015
DOI: 10.1021/ac504191m
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Ion Yields in Time-of-Flight-Secondary Ion Mass Spectrometry: A Comparative Study of Argon and Water Cluster Primary Beams

Abstract: Following from our previous Letter on this topic, this Article reports a detailed study of time-of-flight-secondary ion mass spectrometry (TOF-SIMS) positive ion spectra generated from a set of model biocompounds (arginine, trehalose, DPPC, and angiotensin II) by water cluster primary ion beams in comparison to argon cluster beams over a range of cluster sizes and energies. Sputter yield studies using argon and water beams on arginine and Irganox 1010 have confirmed that the sputter yields using water cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 55 publications
6
102
0
Order By: Relevance
“…This finding is in agreement with recently published studies in the static SIMS regime, which state that high energy and larger clusters are beneficial for increasing the molecular ion yield of organic materials. 15,18 ■ EXPERIMENTAL SECTION Material and Sample Preparation. Presliced 5 mm × 5 mm Si wafers (Ted Pella Inc., Reading, CA, USA) were used as substrates for all films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This finding is in agreement with recently published studies in the static SIMS regime, which state that high energy and larger clusters are beneficial for increasing the molecular ion yield of organic materials. 15,18 ■ EXPERIMENTAL SECTION Material and Sample Preparation. Presliced 5 mm × 5 mm Si wafers (Ted Pella Inc., Reading, CA, USA) were used as substrates for all films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8,9,[18][19][20] The results indicate that in the singlecomponent samples, the ionization of both molecules is enhanced with the (H 2 O) n þ ion beam, particularly with larger water clusters (Fig. 2).…”
Section: A Analysis Of Single-component Samplesmentioning
confidence: 90%
“…Water cluster ion beams were obtained by generating water steam that effused through a heated GCIB nozzle forming clusters in the jet expansion, which are then ionized by electron impact. 9 The study performed a comparison of secondary ion yield obtained with different ion beams on pure and binary mixtures. Secondary ion yields are defined as number of detected secondary ions per primary ion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial version of this source employs 1M Acetic acid solution which are first generated in atmospheric conditions, and then introduced to vacuum conditions through a series of differential pumping apertures, and postaccelerated to the target plate with ~10 kV 114 shown that water clusters could be generated in a nature similar to argon clusters by employing water vapor instead of argon gas 119 . H2O GCIB has been compared to C60 + and Ar2000 + , providing enhanced intact molecular ion yields in comparison to both of these projectiles 120 .…”
Section: Figure 6 Schematic Of An Iontof Argon Gas Cluster Primary Imentioning
confidence: 99%